2021
DOI: 10.1016/j.genhosppsych.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of virtual reality in the inpatient rehabilitation of COVID-19 patients

Abstract: Introduction Use of virtual reality (VR) in healthcare has expanded in recent years. The challenges faced by patients with prolonged COVID-19-related hospitalizations – social isolation, disability, neurologic sequelae, adjustment-related anxiety, depression, and stress – may be mitigated by the novel use of VR as one modality of a comprehensive rehabilitation plan. This descriptive study aimed to understand patient satisfaction and perceived benefit of virtual reality on a COVID-19 recovery unit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 21 publications
2
66
0
1
Order By: Relevance
“…A majority (72.7%) of the studies were conducted in China, including 5 in China's Hubei province, which is where the virus is first known to have been discovered ( Centers for Disease Control and Prevention, 2021 ). Other study sites include India (1; Jerrin et al, 2021 ), South Korea (1; Kim et al, 2020 ), the United States (1; Kolbe et al, 2021 ), and Iran (1; Satoudeh et al, 2020 ), which demonstrates a dearth in research into treatment for COVID-19 patients and survivors from most regions of the world.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority (72.7%) of the studies were conducted in China, including 5 in China's Hubei province, which is where the virus is first known to have been discovered ( Centers for Disease Control and Prevention, 2021 ). Other study sites include India (1; Jerrin et al, 2021 ), South Korea (1; Kim et al, 2020 ), the United States (1; Kolbe et al, 2021 ), and Iran (1; Satoudeh et al, 2020 ), which demonstrates a dearth in research into treatment for COVID-19 patients and survivors from most regions of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Telephone-based interventions may be highly successful in this patient population, with low withdrawal and refusal rates. Kolbe, Jaywant, Gupta, Vanderlind, & Jabbour (2021) Virtual Reality-based Mindfulness Intervention Applied VR's SootheVR headset provides guided medication sessions in highly realistic, three dimensional natural settings, and sessions where patients can passively and actively explore a variety settings (e.g., swimming with dolphins, or exploring world cities). Patients were not given tasks so as to maintain their autonomy as a therapeutic aspect of the experience.…”
Section: Methodsmentioning
confidence: 99%
“…VR has advanced significantly in the healthcare field in recent years, functioning as an instructional tool, a pain distraction measure, and an extra platform for delivering evidence-based interventions such as mindfulness in neurorehabilitation and psychotherapy. The current study in the literature found that implementing this innovation in a hybrid medicine–rehabilitation inpatient unit resulted in a very positive reaction [ 42 , 64 ].…”
Section: Implications For Expanding the Use Of Vr In Communities Expe...mentioning
confidence: 99%
“…Table 1 illustrates the characteristics of the studies with a list of information on the names of studies, year of studies, country of origin, inclusive and exclusive criteria, outcome measures, interventions, and the benefits/disadvantages of VR interventions [ 47 , 57 , 58 , 59 , 64 , 65 ].…”
Section: Implications For Expanding the Use Of Vr In Communities Expe...mentioning
confidence: 99%
See 1 more Smart Citation